Comparison of the effects of polyethylene glycol and hyaluronic acid in prevention of epidural fibrosis - Karabulut, Enis; Karaavci, Funda Aksunger; Eroksuz, Hatice (Hokkaido Univ, 2018)
The aim of this study was to evaluate of the effect of 5% Polyethylene Glycol 4000 in the prevention of epidural fibrosis and to compare the results with hyaluronic acid. A total of 36 adult New Zealand White Rabbits were used in the study. Three groups were formed with each group including 12 rabbits (Group I: Control, Group II: 5% Polyethylene Glycol 4000, Group III: Hyaluronic acid). Hemilaminectomy was performed at L5 vertebrae on the right side. Three rabbits randomly selected from each group at postoperative 2nd, 4th, 8th and 12th week were euthanized. Macroscopic and histopathological evaluation were performed in terms of the amount of scar tissues. Statistical evaluation was made with Mann-Whitney U Test and Kruskal-Wallis Variance Analysis. P < 0.05 was considered statistically significant. In the hemilaminectomy sites of Group I, severe thickness and tenacious epidural scar adhesions were found between the dura mater and surrounding tissues. In the Group II, dura mater was clean without any evidence of adhesion or scar tissue and minimal adhesions were present. In the Group III, moderate adhesion and scar tissue or minimal adhesion and very thin scar tissue were observed. Statistically; Group II was significantly different from Group I (P < 0.000) and Group III (P < 0.002), and Group III was significantly different from Group I (P < 0.001). It was concluded that 5% Polyethylene glycol 4000 can safely be used locally during operation in the area of decompression in order to prevent epidural fibrosis encountered as a postoperative complication after hemilaminectomy.
Keywords: Epidural fibrosis; hemilaminectomy; hyaluronic acid; polyethylene glycol; prevention